2022
DOI: 10.1037/emo0000851
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing, discriminating, and labeling emotional expressions in a free-sorting task: A developmental story.

Abstract: Recognizing emotional expressions across different people and discriminating between them are important social skills. We examined their development using a novel free-sorting task in which children (aged 5 to 10) and adults sorted 20 faces (posing sadness, anger, fear, and disgust) into piles such that all faces in each pile were feeling the same. Participants could make as many or few piles (emotion categories) as they liked and then labeled each pile. There were no age-related changes in the number of piles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Second, facial impressions do not fully mature until around 10 years of age (Siddique et al, 2022), a pattern partially attributable to prolonged development of adult‐like perception of facial displays of emotion. Infants differentiate positive versus negative emotions, but the ability to accurately differentiate negatively valenced emotions takes many years to become adult‐like (Matthews et al, 2022; Widen & Russell, 2008). Given the influence of facial expressions on first impressions (e.g.…”
mentioning
confidence: 99%
“…Second, facial impressions do not fully mature until around 10 years of age (Siddique et al, 2022), a pattern partially attributable to prolonged development of adult‐like perception of facial displays of emotion. Infants differentiate positive versus negative emotions, but the ability to accurately differentiate negatively valenced emotions takes many years to become adult‐like (Matthews et al, 2022; Widen & Russell, 2008). Given the influence of facial expressions on first impressions (e.g.…”
mentioning
confidence: 99%
“…The present data uncover a similar pattern of finer‐grained differentiation across development for emotion knowledge. We found that children first use broad, primarily valence‐based distinctions, and with greater experience, draw more fine‐grained distinctions that use emotion category information (Matthews et al, 2020; Widen, 2013). Rather than a distinct shift from using valence to using emotion categories, we found continued and refined use of valence and emotion categories across development.…”
Section: Discussionmentioning
confidence: 87%
“…” ( Nelson & Russell, 2011 ; Widen & Russell, 2003 ). Other common methods include sorting images into labeled piles ( Hoemann et al, 2021 ; Matthews et al, 2020 ), confirming whether labels match an image displayed with prompts such as “ Is this person feeling sad? ” ( Widen & Russell, 2008 ), or selecting a stimulus from an array of predetermined response options ( Chronaki et al, 2015 ; Leitzke & Pollak, 2016 ; Pollak & Sinha, 2002 ).…”
mentioning
confidence: 99%
“…The use of an emoji was related to more positive interpretations of teasing texts. The specific emoji used, the “winking face with tongue,” combines two facial expressions (i.e., the wink and the sticking out tongue) which could make it more effective in conveying emotions (Matthews et al, 2022) or other nonverbal cues (Dynel, 2008). In support of such a view, the same neurological processing involved in the decoding of irony has been associated with the processing of the “wink” emoji (Weissman & Tanner, 2018).…”
Section: Discussionmentioning
confidence: 99%